Immune-Mediated Thrombotic Thrombocytopenic Purpura: A Narrative Review of Diagnosis and Treatment in Adults - Blennerhassett, Richard; Curnow, Jennifer; Pasalic, Leonardo (Seminars in Thrombosis and Hemostasis, 2020)
Immune-mediated thrombotic thrombocytopenic purpura (iTTP) is a rare and potentially lethal disease characterized by fragmentary hemolysis, moderate-to-severe thrombocytopenia, end-organ dysfunction, and severely reduced ADAMTS13 levels (< 10%). Survival in iTTP has improved significantly since the introduction of plasma exchange as standard therapy combined with immune suppression to address the underlying pathophysiology. A host of challenges remain including prompt recognition of the disease, treatment of the end-organ effects of the disease, improving the early mortality rate, significantly reducing the relapse rate as well as addressing refractory disease. Discussed in this narrative review of iTTP are the recent measures aimed at addressing these issues, including improvements in clinical prediction models, postremission maintenance approaches with early retreatment as well as the development of novel therapies.
Keywords: thrombocytopenic purpura; thrombotic microangiopathy; ADAMTS13; plasma exchange